Pengaruh Harga, Promosi, dan Kualitas Layanan Terhadap Loyalitas Dengan Kepuasan Konsumen Sebagai Variabel Mediasi (Studi Kasus Mahasiswa Pengguna Aplikasi Gojek Di Kota Malang) - Bayu, Juli Adriano; Mardani, Ronny Malavia; Hardaningtyas, Ratna Tri (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to examine the effect of price, promotion and service quality on consumer loyalty with customer satisfaction as a mediating variable case study on Gojek application user students in Malang City. The type of population to be studied is unlimited, because researchers do not know the exact number. Sampling is done by purposive sampling method with 20 x 5 = 100 respondents. Data analysis tools used Partial Least Square version 4.0. Price, Promotion, Service Quality and Customer Satisfaction have a significant effect on Customer Loyalty. Consumer Satisfaction does not mediate Consumer Loyalty, Promotion, and Service Quality. Keywords: Price, Promotion, Service Quality, Customer Loyalty, and Customer Satisfaction